Modification methods for infilled RC frames with and without openings with slides and formed steel: Experimental study. (1st October 2022) - Wei, Yuliang; Zhai, Changhai; He, Yiting; Jin, Wei; Xie, Lili
Abstract: In this article, four pseudo-static tests of infilled RC frames were performed, including an unmodified solid infilled RC frame, an unmodified infilled RC frame with opening and two innovative structural designed specimens for the two original ones respectively. The solid bricks were made of rice husk and Magnesium oxysulfate cement, which is a recently developed environmental friendly thermal insulating material in China. The results of the tests showed that the two modified infilled RC frames provided better seismic performance than two original specimens in ductility, out-of-plane stability, stiffness degradation, etc. The modification also diminished the short-column effect of the infilled frames with opening. Highlights: Two modification methods were proposed for infilled RC frames with and without opening. Four tests were performed to prove that the modified infilled RC frames are better at ductility, lateral stiffness, etc. Crack pattern, failure mode and hysteretic behavior of four specimens were discussed and compared with each other. The short-column effect of the specimens with opening was discussed according to the tests results.